165PLenvatinib treatment for advanced hepatocellular carcinoma: The relationship between efficacy and safety. (24th November 2019) - Oikawa, T; Yusa, K; Okamoto, T; Yonezawa, M; Satou, T; Abe, T; Endo, K; Sawara, K; Kuroda, H; Takikawa, Y
Abstract: Background: Lenvatinib is a new first-line molecular target drug for hepatocellular carcinoma (HCC) that is available worldwide. We evaluated the efficacy and safety of lenvatinib for unresectable HCC. Methods: This study population included thirty-seven patients that we could follow from 42 patients who received lenvatinib between April 2018 and May 2019 in our hospital. We evaluated the lenvatinib treatment profile, the clinical response (according to mRECIST), adverse events (according to CTCAE v.4.0), progression free survival (PFS), overall survival (OS), conversion therapy and the tumor response after progressive disease (PD) and serious adverse events (sAEs). Results: The study population included 34 male patients (91.9%). Eleven patients were positive for HBV, 14 were positive for HCV, 6 had a history of alcohol intake. The Child Pugh scores (CPS) were as follows: 5 (n = 27), 6 (n = 7), 7(n = 3). Fifteen patients had BCLC stage B and 22 had C. The reasons for lenvatinib included TACE failure/refractoriness (35.3%), vascular invasion (32%), extrahepatic spread: (27.0%), PD after other molecular target therapies (16.2%) . The initial dose was 12 mg (90%) in patients with a body weight of > 60 kg, 8 mg (68.8%) in patients with a body weight of < 60 kg; in these two groups, 50.0% and 66.6% of patients received a half-dose reduction after one month. The tumor responses were classified as follows: objective response rate (ORR), 35.1%; disease control rate (DCR), 70.3%; PFS, 7.3 months (95% CI 4.9-11.2); OS, the median OS was not reached. There was no significant differences in the CPS between before and after therapy (p = 0.68). The rates of AEs (any grade/grade ≥3) were as follows: hypertension (37.8/0%), protein urea (29.7/13.5%), hypothyroidism (16.2/0%), fatigue (8.1/2.7%), hand-foot skin reaction (5.4/0%), hepatic encephalopathy (8.1%), respectively. The ORR and DCR of the grade ≥3 and grade <2 groups did not differ to a statistically significant extent. In the grade ≥3 group, 4 patients obtained a clinical benefit, however could not receive chemotherapies because of a poor performance status (≥3). Conclusions: Lenvatinib is good therapeutic drug for advanced HCC, however it is very important to pay attention to sAEs in patients who show a clinical benefit. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.